1987
DOI: 10.1073/pnas.84.4.969
|View full text |Cite
|
Sign up to set email alerts
|

Images of a lipid bilayer at molecular resolution by scanning tunneling microscopy.

Abstract: The molecular structure of a fatty acid bilayer has been recorded with a scanning tunneling microscope operating in air. The molecular film, a bilayer of cadmium icosanoate (arachidate), was deposited onto a graphite substrate by the Langmuir-Blodgett technique. The packing of the lipid film was found to be partially ordered. Along one axis of the triclinic unit cell the intermolecular distance varied randomly around a mean of 5.84 A with a SD of 0.24 A. Along the other axis the mean distance was 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…In addition to the lateral and vertical tip forces (37) which can have distorting effects on biological specimens, a number of other tip-surface interactions which produce spatial distortions have been recognized and include the following: tip shape, which acts to broaden convex structures and narrow concave structures (36); tip switching, which produces multiple images (11); tip-absorbed contaminants, which produce false images (16,19,36); capillary condensation of water vapor at ambient pressures, which reduces the height measurement and possibly deforms the surface of the specimen (40); and scanning speed and feedback gain, which may result in electrical interference and structural artifacts (36). Tunneling current in particular is sensitive to the conductive properties of the surface (13,20,27), and consequently, STM height errors from 20 to 70% have been reported (14). To overcome imaging problems associated with poor conductivity of biological material, Guckenberger et al (17) found that a small but sufficient conductivity from biological material can be induced at humidities of between 30 and 45%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the lateral and vertical tip forces (37) which can have distorting effects on biological specimens, a number of other tip-surface interactions which produce spatial distortions have been recognized and include the following: tip shape, which acts to broaden convex structures and narrow concave structures (36); tip switching, which produces multiple images (11); tip-absorbed contaminants, which produce false images (16,19,36); capillary condensation of water vapor at ambient pressures, which reduces the height measurement and possibly deforms the surface of the specimen (40); and scanning speed and feedback gain, which may result in electrical interference and structural artifacts (36). Tunneling current in particular is sensitive to the conductive properties of the surface (13,20,27), and consequently, STM height errors from 20 to 70% have been reported (14). To overcome imaging problems associated with poor conductivity of biological material, Guckenberger et al (17) found that a small but sufficient conductivity from biological material can be induced at humidities of between 30 and 45%.…”
Section: Resultsmentioning
confidence: 99%
“…An important control for assessing the quality of topographical detail is to utilize structural landmarks or barrier heights for the positive identification of biomacromolecules in scanned images (15,25). Highly ordered biological surfaces (10,16,27,36,37), such as the paracrystalline proteinaceous structures examined in this study, provide mechanically rigid surfaces that contain useful landmark features for assessing image quality. From our TEM characterization of M. hungatei and its envelope structures, we could assess the quality of our STM and AFM images during scanning.…”
Section: Resultsmentioning
confidence: 99%
“…At present, high resolution STM images of a film of phospholipid in solution can be acquired for a monolayer only. However, molecular resolution STM images of a phospholipid bilayer supported at a conductive surface in air have already been reported (28)(29)(30). With further methodological improvements, imaging of the supported bilayer in a solution should also be possible in the future.…”
mentioning
confidence: 99%
“…29 The uneven coverage of the hydrophobic surface and the formation of multilamellar islands make this technique unsuitable for exact bilayer partitioning studies where a well-defined system is needed. The Langmuir-Blodgett technique 30 produced a phospholipid monolayer on the surface of gold-coated plates with covalently attached octadecyl chains. 31,32 The obtained monolayer was uniform and stable in both dry and rehydrated forms.…”
Section: Supported Monolayer Systemsmentioning
confidence: 99%